PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.3 SMP MUHAMMADIYAH 2 PEKANBARU - Sari, Irma; Suanto, Elfis; Saragih, Sehatta (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve learning process andto increase mathematics achievementwith appliedthe learning model of Problem Based Learning. The subject of this research is student of class VIII.3 SMP Muhammadiyah 2 Pekanbaru in the secondsemester academic years 2017/2018, which amounted to 25 students. The research consisit of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection.At the end of every cycle the quiz will be implemented. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The analysis result of observation sheets indicated the learning process in cycle I were better than learning process in before action and learning process in cycle II were better than learning process in cycle I. Most of students were very confidenced and actived in learning process,such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to quiz I and II. The results of this research showed an increasing number of students learning mathematicsabout knowledge of the basic score (20%)to the first quiz (56%) to the second quiz II (80%). Results of this research indicates that appication of the learning model of Problem Based Learning can improve learning process and increase mathematics achievementfrom the students at class VIII.3 SMP Muhammadiyah 2 Pekanbaru in the second semester academic years 2017/2018.Key Words: Mathematics Achievement, Problem Based Learning, Class ActionResearch